1987
DOI: 10.1128/jcm.25.9.1789-1790.1987
|View full text |Cite
|
Sign up to set email alerts
|

Association of Malassezia pachydermatis with systemic infections of humans

Abstract: Thirty-two Malassezia spp. isolates from human clinical specimens represented M. furfur and M. pachydermatis. Both species reportedly were obtained from patients with similar febrile systemic syndromes, including infections of the lungs or other tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 6 publications
0
41
0
2
Order By: Relevance
“…M. pachydermatis, occurring in a wide range of warmblooded animals [27], has been isolated from healthy human skin and from neonates in intensive care units [5,9,14,28,47,48]. The clustering of nosocomial isolates of M. pachydermatis together with isolates originating from pets in our AFLP analysis suggests that little genetic variation occurs within our sample.…”
Section: Aflp Tm and Rapdmentioning
confidence: 81%
“…M. pachydermatis, occurring in a wide range of warmblooded animals [27], has been isolated from healthy human skin and from neonates in intensive care units [5,9,14,28,47,48]. The clustering of nosocomial isolates of M. pachydermatis together with isolates originating from pets in our AFLP analysis suggests that little genetic variation occurs within our sample.…”
Section: Aflp Tm and Rapdmentioning
confidence: 81%
“…Malassezia species have been associated with deepseated infections such as catheter-related fungemia, especially in neonates [31,32,[91][92][93]. M. pachydermatis, earlier exclusively considered to be associated with animals, has been reported to cause intravascular catheter-acquired infections in humans [31,32].…”
Section: Other Disordersmentioning
confidence: 99%
“…Several reports suggested that M. sympodialis is the predominant species in healthy human skin and skin of patients with atopic dermatitis, while M. globosa was found in PV. [6][7][8][9][10][11] M. restricta, rarely isolated from the upper trunk and relatively frequently isolated from the forehead and scalp, seems to be associated with seborrheic dermatitis and psoriasis. 6 is known as an agent of external otitis and has been considered responsible for some cases of systemic infection in premature children.…”
Section: Discussionmentioning
confidence: 99%
“…6 is known as an agent of external otitis and has been considered responsible for some cases of systemic infection in premature children. 11 While most studies suggest that M. globosa is a causative agent of PV, several studies showed that M. sympodialis and M. furfur were the predominant species in PV. [14][15][16] The difference in distribution of Malassezia species among studies in the results yielded by the conventional culture-based method may be attributed to the sampling technique and different culture media.…”
Section: Discussionmentioning
confidence: 99%